Neuro-Evolutionary Foundations of Infant Minds: From Psychoanalytic Visions of How Primal Emotions Guide Constructions of Human Minds toward Affective Neuroscientific Understanding of Emotions and Their Disorders. Issue 1 (2nd January 2019) - Panksepp, Jaak; Clarici, Andrea; Vandekerckhove, Marie; Yovell, Yoram
ABSTRACT: As Louis Sander understood, human infants are evolutionarily endowed with emotional minds that allow them to experience themselves as affectively vibrant creatures, who seek to be recognized as important players in the world. If so recognized, they experience themselves as positive individuals; if merely neglected as predetermined beings whose affects and intentions do not matter in the long-term construction of their minds, paths toward adult disturbance are paved. The neuroscience of affective processes has been substantively advancing through the use of animal models where the needed detailed experimental work can be conducted. Critical neural networks and neuro-epigenetic brain changes are being documented that provide neuroscientific confirmations for the insights advanced by Sander and his many colleagues. Here we show how the deeply intersubjective, flexible nature of the mother-infant relationship is firmly expressed in the underlying biology of the basic limbic emotional systems. Rather than being deterministic, hard-wired affective switches, these emotional systems (e.g., CARE, PLAY, PANIC, SEEKING, RAGE, FEAR, and LUST) are modulated by (and, in turn, modify) the developing relationship between mother and infant. Thus, the nature-nurture debate can be meaningfully reconceptualized as a bio-psycho-social interactive model, in which biology shapes relationships, which, in turn, shape and sometimes radically modify the biology.